Immature embryo: A useful tool for oil palm (Elaeis guineensis Jacq.) genetic transformation studies - Abdullah, Ruslan; Zainal, Alizah; Wee, Yew Heng; Leaw, Chui Li; Yeap, Chee Beng; Lee, Mei Phing; Abdullah Sirajuddin, Salwa; Yap, Winnie Soo Ping; Joseph, Juanita Lourdes; Jusoh, Siti Azma (Pontificia Universidad Católica de Valparaíso -- Chile, 2005)
Oil palm (Elaeis guineensis Jacq.) is the highest yielding oil-bearing crop. However, being a perennial crop, genetic improvement of oil palm is extremely slow. Indeed, compared to other annual oil crops such as soybean and rapeseed, genetic manipulations remained less important. Therefore, to remain competitive, oil palm growers and breeders need new and novel approaches. In this report, the potential of immature embryos (IE) as a useful tool for oil palm genetic transformation studies was evaluated. It was evident that IEs were amenable to both direct and Agrobacterium-mediated gene transfer. Due to the abundant supply of IE, optimization of biolistic and Agrobacterium-mediated gene transfer into IEs were easily carried out. Transient transformation frequencies were comparable to other plant systems reported, with as high as 97.4% recorded for biolistic and 64.4% for Agrobacterium-mediated gene transfer. Like most moncots, oil palm tissues were less sensitive to kanamycin, geneticin and chloramphenicol. Instead, both hygromycin and phosphinotrycin were toxic 20 mg/l, making both suitable candidates for selecting putative transformants. IEs were also more responsive to in vitro manipulations as compared to other explants such as leaf and root tissues. Rapid in vitro response to callusing and embryogenesis or rapid and highly efficient direct germination resulted in a shorter culture period. This would minimize the production of abnormal clonal palms, which has been associated to chromosomal aberration due to prolonged time in culture. In addition, IEs also allows rapid and direct introduction of elite genes into breeding programs and in biclonal seed production.